Sensory Quality Analysis Traditional Ginger Wedang Beverage Made From Red Ginger - Gebby Junaichi; Lise Asnur (Universitas Negeri Padang, 2026)
Traditional drinks are part of the Indonesian cultural heritage that has cultural, sensory, and development potential development as a culinary product. One of the traditional drinks that are still consumed is wedang ginger. This study aims to describe the quality of sensory drinks traditional wedang ginger-winged ginger which includes color, aroma, taste, and overall revenue level. This research uses quantitative descriptive approach with product-specific experiment stage using one-default exploration result recipes.Sensory quality testing is done through organoleptic tests with a five-level hedonic scale. The panelist involved amounted to 30 untrained panelists who assessed the sensory attribute of Wedang Ginger made of red ginger. The data obtained were analyzed descriptively using the average value and grouping of the category of the level of the site. The results showed that the wedang ginger made from red ginger has reddish brown characteristics, ginger scents strong enough to strong, warm spicy, and the overall level of acceptance in the category is favored by the panelists. Based on these results, it can be concluded that the ginger wedang made from red ginger has good sensory quality and potentially developed as traditional drinks acceptable to consumers.